2000
DOI: 10.1051/rnd:2000101
|View full text |Cite
|
Sign up to set email alerts
|

Rumen effective degradability of amino acids from soybean meal corrected for microbial contamination

Abstract: -Rumen degradation kinetics and effective degradability of individual amino acids, total analysed amino acids (TAA) and crude protein (CP) of soybean meal were measured on four rumencannulated wethers using the nylon bag technique. Microbial contamination of the incubated residues was corrected using a continuous 15 N intraruminal infusion and isolated solid associated bacteria as a reference sample. TAA showed a lower soluble fraction (14.9 vs. 20.8%; P < 0.01), a similar insoluble-degradable fraction (79.0 v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
2
3
0
Order By: Relevance
“…The estimates of ED for BCAA and Phe in EP and HS were higher than values for the other EAA; furthermore, the ED for BCAA and Phe was not constant across SBM products. Other studies have also reported differences in AA composition of the RUP from SBM compared with the original feed protein (Crooker et al, 1987;Gonzá lez et al, 2000). The present study, with several rumenprotected products, confirms that not only are there differences in the effective degradation between CP and EAA, but also that there are differences in ED among the individual EAA.…”
Section: Rumen Kineticssupporting
confidence: 84%
“…The estimates of ED for BCAA and Phe in EP and HS were higher than values for the other EAA; furthermore, the ED for BCAA and Phe was not constant across SBM products. Other studies have also reported differences in AA composition of the RUP from SBM compared with the original feed protein (Crooker et al, 1987;Gonzá lez et al, 2000). The present study, with several rumenprotected products, confirms that not only are there differences in the effective degradation between CP and EAA, but also that there are differences in ED among the individual EAA.…”
Section: Rumen Kineticssupporting
confidence: 84%
“…Degradation rate values also showed a high apparent increase for TAA. This fact was also observed for soybean meal by González et al (2000), who associated it with the nitrogenous compounds bounded to the fibre fraction. These compounds will be slowly degraded and, when they are proteins, they could be resistant to the hydrolysis and therefore not detected in the chromatographic analysis.…”
Section: Discussionsupporting
confidence: 61%
“…Duodenal flows of Arg and Leu in the T group were significantly (P<0.05) higher. These results are correlated with a relatively high content of these amino acids in soya bean protein (Gonzáles et al, 2000). Due to the rumen protection of mixture duodenal flows of free Met, Lys, His and Arg increased by 3.6, 2.7, 4.4 and 2.5 times, respectively, against the control.…”
Section: Discussionmentioning
confidence: 61%